Waiver of Consent in a Trial Intervention Occurring at Birth—How Do Parents Feel? - Rich, Wade D.; Katheria, Anup C. (Frontiers in Pediatrics, 2017)
Background: We have previously demonstrated that it is difficult to obtain a representative subject sample when conducting a randomized controlled trial (RCT) at or near the time of birth and obtaining antenatal consent. Deferred consent has been used in neonatal trials, but parents’ reactions to being enrolled in these trials have never been reported. Methods: The parents enrolled in a RCT involving a waiver of consent with a post-delivery discussion were asked to take part in a brief survey. The survey questions included the timing of when parents were informed about the study, and how they felt about their infants being included in the study. Results: Forty-nine (49) parents completed the online survey. Sixty-nine percent (n=34) remembered a physician discussing their premature baby with them prior to delivery. Thirty-four percent (17) indicated the physician had discussed participation in the study prior to delivery. Sixty nine percent (34) indicated that they had a positive or strongly positive feeling about the studies impact on their baby’s health. Conclusions: Our study demonstrates that the majority of responding parents of infants who have actually participated in a RCT with a waiver of consent process had a positive response, a minority had a neutral response, and none had a slightly negative or highly negative response to participation in the study.